2019
DOI: 10.1002/app.48154
|View full text |Cite
|
Sign up to set email alerts
|

Improving the ductility of polylactic acid parts produced by fused deposition modeling through polyhydroxyalkanoate additions

Abstract: Polylactic acid (PLA) is one of the most commonly used materials for fused deposition modeling (FDM) due to its low cost, biocompatibility, and desirable printing characteristics. However, its low ductility is a major disadvantage for engineering applications where high damage tolerance is needed. This study investigates the feasibility of polyhydroxyalkanoate (PHA) additions to PLA for improving the ductility of parts produced by FDM. Thermal and mechanical behavior of PLA/PHA specimens containing 12 wt % PHA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 37 publications
3
30
0
Order By: Relevance
“…The extent of crystallization and the microstructure would depend on the nozzle temperature and filament chemistry. Previous work on FDM‐produced PLA‐PHA blend specimens has shown that such microstructural changes can influence the strength and ductility, by altering the crystallinity of each phase 16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extent of crystallization and the microstructure would depend on the nozzle temperature and filament chemistry. Previous work on FDM‐produced PLA‐PHA blend specimens has shown that such microstructural changes can influence the strength and ductility, by altering the crystallinity of each phase 16 …”
Section: Discussionmentioning
confidence: 99%
“…For the reliable operation of these FDM‐produced engineering parts, there is a need to understand the effect of FDM process parameters on the mechanical properties. Especially the process parameters such as nozzle temperature, specimen orientation, and raster orientation have a direct impact on mechanical performance 14–17 . In the last decade, there has been a considerable amount of research on the structure‐process‐property relationships for primary filament materials such as Acrylonitrile butadiene styrene (ABS) and PLA, providing a detailed understanding of the mechanical properties of FDM‐produced parts 2,18 .…”
Section: Introductionmentioning
confidence: 99%
“…where w (g) stands for the weight fraction of PLA and ∆H m o (J g −1 ) represents the theoretical melting enthalpy of a fully crystalline PLA polymer, which is close to 93.7 J g −1 [46][47][48][49].…”
Section: Thermal Characterizationmentioning
confidence: 96%
“…The existence of these restricts the lamellar thickening, accounting for the thinner crystal lamellae (Figure 5D) Finally, some crosslinked points distributed in the interspherulitic or interlamellar regions result in enhanced connectivity among spherulites and crystal lamellae. Both thinner crystal lamellae and smaller spherulites endow PVDF with excellent ductility [42]. The better connectivity among crystals is beneficial to the improvement of strength.…”
Section: Resultsmentioning
confidence: 99%